Acne and Acneiform Eruptions - Pelin Kartal, Selda; Gonul, Muzeyyen (IntechOpen, 2017)
The aim of this book is to give readers a broad review of acne vulgaris and acneiform dermatoses, which may affect people from birth to death, and their treatment options. This book has a total of 14 chapters. The "Introductory Review" chapter focuses on the terms "acne" and "acneiform," one of which is a multifactorial disease of pilosebaceous unit and the other refers to dermatoses, which resemble acne vulgaris clinically but have different etiopathogenesis. Other 13 chapters are created by experts in different fields like dermatology, dermatosurgery, pathology, and ophthalmology. This book is easy to read and it includes illustrations, tables, patient photographs, and histopathological slides to support the written text and to enhance the reader's understanding. We are grateful to all the contributors and leading experts for their valuable chapters, which provide an in-depth view of all aspects of the content, backed with the most current literature in the field.